Pengaruh Ekstensifikasi Pajak, Intensifikasi Pajak, Kenaikan PTKP, Dan Tax Holiday Terhadap Penerimaan Pajak Orang Pribadi Di Jakarta Barat - Ngadiman Ngadiman; Felicia Felicia (Jurnal Akuntansi, 2017)
The purpose of research is to determine the influence of tax extensification, taxintensification, non-taxable income increases, and tax holiday to individual tax income.This research was conducted to 100 individual taxpayers respondents in Jakarta Barat.This research uses multiple linear regression models to test the hypothesis. The result ofthis research shows that tax extensification, tax intensification and non-taxable incomeincreases have significant influence to individual tax income. While taxholiday has nosignificant influence to individual tax income.